Feasibility of calcium hydroxyapatite (Radiesse®) for improving the biomechanical properties of facial burn scars: A pilot study - Mariana del Carmen Radilla-Flores; Erik Agustín Márquez-Gutiérrez; Mario Vélez-Palafox; María Isabel Castrejón-Vázquez; Osiris Cristina Chávez-Flores; Mario Chopin-Doroteo; Maykel González-Torres (JPRAS Open)
Background: Effective treatments for facial burn scars remain limited, emphasizing the need for innovative therapeutic approaches. This study explored the feasibility of the use of calcium hydroxyapatite (CaHA, Radiesse®) as a treatment to improve the biomechanical properties of facial burn scars. Objective: To evaluate the potential effects of CaHA injections on the biomechanical properties of facial burn scars and to compare these effects with those of untreated skin. Methods: A prospective longitudinal feasibility study was conducted with 13 patients who had mature facial scars (2–5 years) covering more than 90% of the face, including hypertrophic, atrophic, and/or keloid scars. The forehead, cheek, and jaw areas were measured before treatment (baseline control) and at 2, 4, and 6 months after CaHA application, resulting in 312 measurements. CaHA was injected subdermally on one side of the face, with the opposite side serving as a control. Biomechanical properties were assessed via a Cutometer MPA 580 alongside clinical assessments, photography, and validated scar scales (Vancouver Scar Scale and Patient and Observer Scar Assessment Scale). Results: Preliminary findings suggest that CaHA injections may improve skin extensibility, elasticity, viscoelasticity, hydration, erythema, and pigmentation in the forehead, cheek, and jaw areas. These observations were supported by visual assessments and scale evaluations. Conclusion: This feasibility study indicated that subdermal CaHA injections have potential as a noninvasive approach for improving the biomechanical properties of facial burn scars. However, further studies with larger sample sizes and long-term follow-up are needed to confirm these findings.